The illustrated guide to assistive technology and devices : tools and gadgets for living independently - Robitaille, Suzanne (New York : Demos Medical Pub, 2010)
Synopsis: Journalist and author Suzanne Robitaille writes extensively on disability issues. She is the farmer assistive technology columnist for BusinessWeek.com, and has also written for The Wall Street Journal, Disohoom.com, Ability Magazine, and more.
Includes bibliographical references and index.
Keywords: Self-help devices for people with disabilities -- United States; Computerized self-help devices for people with disabilities -- United States; Communication devices for people with disabilities -- United States; People with disabilities -- Rehabilitation -- United States